Application of TE151A Hydraulic Pressure Station in Mine Hoist and Its Maintenance - TAO Zhi-yong (Gong-kuang zidonghua, 2011)
The paper introduced composition and working principle of TE151A hydraulic pressure station of mine hoist and expounded daily maintaining methods of TE151A hydraulic pressure station. For common fault phenomenas of TE151A hydraulic pressure station, it analyzed possible fault causes and proposed corresponding solving measures. The paper provides some reference for operating and maintaining workers of TE151A hydraulic pressure station.